Comparative Analysis using Tsukamoto and Sugeno Methods of Fuzzy Inference System for Sales of Medicine - Efendi, Dwi Marisa; Ardhy, Ferly (Journal of Applied Science, Engineering and Technology, 2021)
This case study has been implemented on the apothecary shop located at Kotabumi city at Lampung province, Indonesia that selling various types of medicine. An apothecary in his scientific efforts need by prediction to a hypothetical for determining the amount of in the demand and the purchase of the new term, which has a challenge on increasing the purchasing amount and reflected the bank sound assets. A prediction used was to analyzed from the results of the comparison a method of Tsukamoto and Sugeno by using the nine rules and comparison to the value of absolute error of the purchase. Based on a the Sugeno method, the absolute error of the purchase was 0.0176 %, which is the lowest value in the study.